2015
DOI: 10.3390/nu7105414
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Food Promotion: A Systematic Review on the Influence of the Food Industry on Obesity-Related Dietary Behaviour among Children

Abstract: An increased consumption of energy-dense, nutrient-poor food and beverages as a result of a changing obesogenic environment contributes substantially to the increasing prevalence of childhood overweight and obesity. This paper reviews the nature and extent of food industry influences which expose children to commercial influences and thus might affect unhealthy dietary behaviour and finally contributes to obesity. A systematic search of nine electronic databases (including PubMed, PsycINFO, EconLit) and refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 56 publications
3
52
0
5
Order By: Relevance
“…This study is one of the first to assess targeting of commercial snack products to children under 3 years and their caregivers in Indonesia, and the prevalence of targeting found is concerning. Promotions of commercially produced snack foods and sugar sweetened beverages have been shown to influence purchase and consumption behaviours (Boyland et al, ; Sonntag, Schneider, Mdege, Ali, & Schmidt, ). In our study, promotions for candy/chocolate/jellies and malted beverages/non‐dairy milks, which are often high in added sugar, were found to most frequently use techniques that targeted children.…”
Section: Discussionmentioning
confidence: 99%
“…This study is one of the first to assess targeting of commercial snack products to children under 3 years and their caregivers in Indonesia, and the prevalence of targeting found is concerning. Promotions of commercially produced snack foods and sugar sweetened beverages have been shown to influence purchase and consumption behaviours (Boyland et al, ; Sonntag, Schneider, Mdege, Ali, & Schmidt, ). In our study, promotions for candy/chocolate/jellies and malted beverages/non‐dairy milks, which are often high in added sugar, were found to most frequently use techniques that targeted children.…”
Section: Discussionmentioning
confidence: 99%
“…Food marketing has been found to be a key environmental factor that promotes childhood weight gain. 16 Current evidence yields that food marketing to children is abundant, in multiple venues (e.g., point of sale, television, product placement) and mostly involves energy-dense and nutrient-poor foods. 17 Furthermore, marketing influences children´s brand preferences and taste preferences that favor less healthy foods.…”
Section: Food Marketing and The Obesity Epidemicmentioning
confidence: 99%
“…First, given the complexity of childhood obesity and key obesogenic environments, conventional approaches commonly used in economic evaluations during adulthood may be of limited use [10] . For instance, Sonntag et al [13] have shown that obesityrelated dietary behavior in childhood is influenced not only by parents but also by 5 key obesogenic environments: schools, television, the internet, retailers, and advertising campaigns. A comprehensive economic evaluation must not merely consider the economic consequences of parental behavior on children; it must also capture whether obesity prevention programs mitigate negative effects of key obesogenic environments and how this can be monetarily evaluated.…”
Section: The Economic Burden Of Childhood Overweight and Obesitymentioning
confidence: 99%